2010
DOI: 10.1016/j.rmed.2009.10.007
|View full text |Cite
|
Sign up to set email alerts
|

COPD health care in Sweden – A study in primary and secondary care

Abstract: Special attention to COPD, marked by a specialised nurse in primary care improves the quality, as assessed by a lower number of exacerbations. The structure of COPD care in Sweden for diagnosed individuals seems satisfactory, but could be improved mainly through higher availability and educational activities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
30
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 19 publications
(11 reference statements)
6
30
0
Order By: Relevance
“…According to national criteria for asthma/COPD receptions in primary care [39], a level corresponding to 10 weeks of university supplementary training about asthma and COPD for a COPD nurse is an acceptable level. Two third of the nurses in our study did not reach even half that level and similar results were found in a study covering the whole Sweden [48]. In the subcategory Driving spirit carries COPD care the COPD nurses was described to be main responsible for the spirometry tests, that is required to confirm a COPD diagnosis [1].…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…According to national criteria for asthma/COPD receptions in primary care [39], a level corresponding to 10 weeks of university supplementary training about asthma and COPD for a COPD nurse is an acceptable level. Two third of the nurses in our study did not reach even half that level and similar results were found in a study covering the whole Sweden [48]. In the subcategory Driving spirit carries COPD care the COPD nurses was described to be main responsible for the spirometry tests, that is required to confirm a COPD diagnosis [1].…”
Section: Discussionsupporting
confidence: 60%
“…Meanwhile, earlier Swedish surveys [23, 24, 48] have reported high availability of professionals for rehabilitation in primary care. Access to patient education in groups was low in our study, while earlier studies [23, 24] showed that nearly half of the centres had access to PR-programmes in primary care, while a quarter sent their patients to hospital-based PR-programs [23].…”
Section: Discussionmentioning
confidence: 99%
“…The corresponding rates in non-COPD subjects in the same studies were 33% and 13%, respectively. [35,39] A survey of COPD patients in secondary care (2007) showed that 23% were still smokers [40] compared to national estimates of around 16% (2005) in the whole population (>45 years of age) [37].…”
Section: Methodological Considerationsmentioning
confidence: 99%
“…11 Most PC centers in Sweden have spirometers and specialized asthma/COPD nurses who provide customized care. 10 Annual societal costs of COPD in Sweden in 2010 were estimated at €1.5 billion, and similar to the picture globally, indirect costs were higher than direct costs of the disease, accounting for 65% and 35% of the total costs, respectively. 12 It is important to better understand the economic burden of COPD in Sweden regarding direct and indirect cost drivers, particularly how these costs differ between patients with/without COPD.…”
mentioning
confidence: 80%
“…3 A majority of patients with COPD in Sweden are managed in PC. 10 During an acute exacerbation, patients present at their primary health care center or at the hospital emergency department. 11 Most PC centers in Sweden have spirometers and specialized asthma/COPD nurses who provide customized care.…”
mentioning
confidence: 99%